ANALISIS KEMAJUAN PENYELENGGARAAN KAWASAN EKONOMI KHUSUS GALANG BATANG: ANALISIS KEMAJUAN PENYELENGGARAAN KAWASAN EKONOMI KHUSUS GALANG BATANG - Setyawan, Budhi; Prihatiningrum, Novie (Unit Penerbitan Politeknik Keuangan Negara STAN, 2024)
In order to actualize the vision of National Development as stated in Law no. 17 of 2007 on the Long-Term National Development Plan of 2005-2025, one of the strategies of the Government of Indonesia is through the development of Special Economic Zones. The development of Special Economic Zones must be supported by advanced infrastructure and supporting utilities to accelerate the economy in the SEZ area. In addition, the development of SEZs also requires the provision of incentives needed to invest in SEZs. This study aims to describe the development of infrastructure, the utilization of fiscal incentives and the challenges faced in the development of the Galang Batang Special Economic Zone. This research occupies qualitative approach. The data was collected through literature review and in-depth interview. The result of research shows that infrastructure development in Galang Batang SEZ can be said to be running optimally with consistent and progressive development progress. In addition, various incentives and services provided by the government are able to attract Foreign Direct Investment which is reflected in the investment commitments that have been received by the Galang Batang SEZ. In its implementation, there are still several challenges in the development of the Galang Batang SEZ, both from internal government and external factors. Keywords : fiscal incentives; special economic zones; infrastructure